SYNCHRONIZATION OF SAPI MADURA OVULATION WITH GNRH DAN PGF2 Αα - M Zali; D Sulistyowati; Toha Toha (Jurnal Ilmiah Fillia Cendekia, 2019)
Madura cattle used in this study used PGF2α at a concentration of 2 ml (Group 1.), GnRH + PGF2α + GnRH (Group 2.) and GnRH + PGF2α + ECP (Group 3.) was 100%. This is in accordance with the results of the chi square test on livestock which lust on treatments 1,2 and 3 that the three treatments had a very good lustrous response, but did not show a significant difference in pregnancy (P> 0.05). Pregnancy detection is done by rectal palpation at the age of 2 months after IB is carried out and supported by looking at the profile of the progesterone hormone from blood palsma, if the concentration above 2 nmol / mL is thought to have undergone pregnancy. The results of pregnancy group 1, group 2 and group 3. were very low at 10%, 20% and 20%